2016
DOI: 10.1061/(asce)mt.1943-5533.0001536
|View full text |Cite
|
Sign up to set email alerts
|

Hydric Behavior of Earth Materials and the Effects of Their Stabilization with Cement or Lime: Study on Repair Mortars for Historical Rammed Earth Structures

Abstract: Earthen building materials bear interesting environmental advantages and are the most appropriate to conserve historical earth 7 constructions. To improve mechanical properties, these materials are often stabilized with cement or lime, but the impact of the stabilizers on 8 the water transport properties, which are also critical, has been very rarely evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 20 publications
2
34
1
12
Order By: Relevance
“…A reduction of clay's active surface area generates a double effect on soils: i) an increase in the sorptivity arising from reduced clay swelling [48,49]; ii) a reduced physico-chemical affinity for water, due to the inhibition of clay's high cation-exchange capacity [50]. Considering that no expansive clay was present, a lower active surface area only resulted in a reduction of the soil's affinity for water.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction of clay's active surface area generates a double effect on soils: i) an increase in the sorptivity arising from reduced clay swelling [48,49]; ii) a reduced physico-chemical affinity for water, due to the inhibition of clay's high cation-exchange capacity [50]. Considering that no expansive clay was present, a lower active surface area only resulted in a reduction of the soil's affinity for water.…”
Section: Discussionmentioning
confidence: 99%
“…moist loose soil compacted inside formwork, but the soil mix is stabilised with (most commonly) cement or lime. Cement and lime not only enhance strength but they also reduce the tendency to swell and shrink, to crack and to generate dust [9,10]. In other words, even though traditional RE is characterised by the use of raw minerals with minimal embodied energy (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…RE is a dense material (typically c.1834-2000 kg/m 3 but can vary widely from 1700 to 2200 kg/m 3 [1,7,9,10] with high thermal mass. Therefore, it can absorb and store heat which can subdue large temperature variations and reduce peak heating/ cooling loads becoming a solar passive design.…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors claim that the response to varying humidity differs significantly in different RE walls, and that it is essential to optimise their response to fluctuations in vapour pressure gradients in order to make their humidity buffering functional. Gomes et al [10] showed that adding mineral binders as stabilizers negatively affects the hydric behaviour of earth materials increasing their water absorption and slowing down drying.…”
Section: Introductionmentioning
confidence: 99%